INCOME ANALYSIS OF ISA BROWN’S LAYING HEN FARM FED WITH MAGGOT FLOUR AS A SUBSTITUTE FOR COMMERCIAL CONCENTRATE - N. P. G., Agustya,; Sukanata, I W.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the business income of Isa Brown laying hens given maggots flour in the rations. It was conducted at Arcana Farm located in Candikusuma Village, Melaya District, Jembrana Regency, Bali Province. It was conducted for 8 weeks, starting from preparation to data analysis. The design used was a Complete Random Design (CRD) with four treatments and four replicates, with each repiclate using four chickens so that the total chickens for each treatment were 16 chickens. The treatment given rations without maggot flour (P0), rations added with 3% maggot flour (P1), rations added with 4% maggot flour (P2), and rations added with 5% maggot flour (P3). Variables observed include cost, revenue, income, R/C ratio, and break event point. The results of the income analysis showed that the provision of maggot flour as much as 5% showed the best results with net income of Rp.82.897/month, R/C ratio 1.13, BEP production is 258 eggs, BEP price is Rp.1,479/item and BEP sales is Rp.432,666. Based on the results of the study, it can be concluded that the provision of maggot flour into the ration is able to increase the income and efficiency of the Isa Brown laying hen farming business.